Analysis of the Impact of Toll Road Development on MSME Income: Case Study of Kampar Regency - Hidayat; Rahayu, Heffi Christya; Fajri, Muhammad; Elfira, Roza; Dewi, Hani Permata; Gitya, Febiana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Development is a demand of society to achieve progress and prosperity. This study aims to analyze the impact of toll road construction on the income of MSMEs in Kampar Regency. This study uses a quantitative approach with the data source in this study being primary data derived from questionnaire data collection with field observations. Observations were conducted using interview techniques with respondents from MSME actors who were directly affected by the construction of the Pekanbaru-Bangkinang Toll Road in Kampar Regency. This study analyzes how toll road construction affects accessibility and MSME income, using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to explore the causal relationship between variables. The results of the study indicate that while accessibility mediates the relationship between toll road construction and MSME income, the direct effect of toll road construction is statistically insignificant. These findings indicate that infrastructure alone will not provide optimal benefits for MSMEs without measures such as improving distribution networks and training. The recommendations given in this study are the creation of rest areas for MSMEs, strategic placement of toll exits, and the involvement.